Critical Study of the Meaning of Modernity in Education - Muh. Natsir; Eva Sri Rohani; St Hajrawati; Ismail Usman; Muchlas Khotomi; Suhartina Suhartina; M. Yunus (Journal of Indonesian Progressive Education, 2026)
This study critically examines the meaning of modernity in education, with particular emphasis on the perspective of Islamic education. It aims to analyze the concept of educational modernization, explore the historical background of modernization in Islamic education, identify its key ideas and principles, and examine its implementation in light of educational values, especially Islamic values. Modernity in education is characterized by the rapid advancement of science, technology, and social transformation, which significantly influence educational systems and learning practices. While these developments provide opportunities to improve the quality, effectiveness, and accessibility of education, they also raise challenges in preserving moral values, cultural identity, and character development. Therefore, a critical understanding of modernity is essential to ensure that educational progress is not solely driven by technological advancement but also remains aligned with the fundamental goals of education. This study employed a library research method by reviewing relevant books, scholarly articles, and other academic literature. The findings indicate that educational modernization should be understood as a process of renewal that enhances educational quality and responsiveness to contemporary demands. However, its implementation must be balanced with ethical, spiritual, and character-based values to prevent scientific and technological progress from overshadowing the broader educational mission. The study concludes that modernity should be viewed as an adaptive educational paradigm that integrates innovation with humanitarian, moral, and religious principles, particularly within the framework of Islamic education. Such an approach is expected to foster competent, ethical, and socially responsible individuals capable of addressing the challenges of an increasingly dynamic global society.